THE EFFECT OF ZAKAT MANAGEMENT ACCOUNTABILITY ON MUZAKKI'S INTEREST IN DHUAFA WASPADA WALLETS IN NORTH SUMATRA PROVINCE - Hayati, Isra; Pratiwi, Indah (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to empirically examine the effect of zakat management accountability on muzakki's interest in Dompet Dhuafa Waspada, North Sumatra Province. This study used a quantitative method, in which this research used a questionnaire as a data collection tool which was distributed directly to Muzakki Dompet Dhuafa Waspada Medan, and data analysis techniques used SPSS. The variable used in this study is the independent variable (accountability) while the dependent variable (muzakki's interest). The results of this study indicate that there is an influence between the accountability variable (X2) on muzakki's interest (Y) which is indicated by the tcount value which is greater than the ttable, namely the t count value of 4.484 t table 1.987 so it can be concluded that the Accountability variable (X2) has a positive effect on interest in muzakki (Y). This also means that the accountability provided by Dompet Dhuafa Waspada to muzakki is maximized.